Atmospheric resonances and their coupling to vibrations of the ground and waves in the ocean - Oleg A. Godin; Nikolay A. Zabotin; Liudmila Zabotina (Earth, Planets and Space, 2020)
Abstract Observations of the ionosphere with the airglow, GPS-TEC, and HF radar techniques reveal a resonant response of the middle and upper atmosphere to broad-band excitation by earthquakes, volcano eruptions, and convective storms. The resonances occur at such frequencies that an atmospheric wave, which is radiated at the ground level and is reflected from a turning point in the middle or upper atmosphere, upon return to the ground level satisfies boundary conditions on the ground. Using asymptotic and numerical models of atmospheric waves, this paper investigates atmospheric resonances and their excitation by seismic waves and infragravity waves in the ocean. It is found that “buoyancy” resonances with periods up to several hours arise in addition to “acoustic” resonances with periods of about 3–5 min. The acoustic and buoyancy resonances occur, respectively, on the acoustic and gravity branches of the dispersion curve of acoustic-gravity waves. Buoyancy of the atmosphere is important for the resonances of both kinds. Acoustic resonances are found to be sensitive to the temperature profile, especially around mesopause and tropopause, and are predicted to be a seasonal phenomenon in polar atmosphere. Unlike acoustic resonances, buoyancy resonances exhibit high sensitivity to the wind velocity profile and its variations. The resonances correspond to most efficient coupling between the atmosphere and its lower boundary and are promising for detection of such coupling.